Covalent Patterning of Graphene for Controllable Functionalization from Microscale to Nanoscale: A Mini-Review - Li, Zhi; Li, Kai; Wang, Shuang; Teng, Chao (Frontiers in Chemistry, 2022)
Covalent patterning of graphene opens many application possibilities in the field of photonics, electronics, sensors and catalysis, due to ordered-dependent optical properties, band structure engineering, and solubility and reactivity improvement. Owing to the low reactivity of graphene basal plane, harsh reagents (e.g. radicals) used for covalent functionalization normally result in poor spatial control, which largely compromises the intrinsic properties of graphene. Therefore, precisely spatial control on covalent patterning of graphene is of great importance. Herein, we summarize recent advances for covalent patterning of graphene from micro- to nano-scale resolution using different techniques such as laser or electrochemical writing, template-directed growth and tip-induced nanoshaving.